From description to teaching of relative clauses: The perspective of text books in Portuguese - Pezatti, Erotilde Goreti [UNESP]; Câmara, Aliana Lopes [UNESP] (My University, 2014)
This paper aims at investigating the treatment given to relative clauses by elementary school text books, evidencing how the teaching of grammar is proposed in the teacher's books. As a consequence, this study also intends to discuss important aspects to be considered as far as the teaching of relative clauses is concerned. In order to achieve that objective, five Portuguese text books (approved by the Programa Nacional do Livro Didático-2014) were selected so that the grammar teaching proposals could be analyzed in relation to the definition and to the distinguishing criteria between defining and non-defining relative clauses. Results show that the teaching of relative clauses (as proposed by the teacher's books) still reflects the postulates of the traditional grammar, based on activities of identification and classification of morphosyntactic units, ignoring the pragmatic and prosodic aspects.
Da descriçãoaoensinoda oraçãoadjetiva: A perspectiva dos livros didáticos delíngua portuguesa
Keywords: Functionalism; Grammar teaching; Relative clause; Text book